Revised Ordinances of 1892 of the City of Boston 115 (1895) - (:unkn) unknown (My University, 1895)
§ 91: No person shall manufacture or sell, or expose for sale, any guncotton, nitro-glycerine, or any compounds of the same, nor any fulminate or substance, except gunpowder, intended to be used by exploding or igniting it, in order to produce a force to propel missiles, or to rend substances apart, except in accordance with a permit from the board of fire commissioners; nor shall any person send or carry through the public streets any such substance, except in the manner and in the quantities allowed by statute or ordinance.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES